2018
DOI: 10.1038/s41467-018-04949-4
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline-intercalated manganese dioxide nanolayers as a high-performance cathode material for an aqueous zinc-ion battery

Abstract: Rechargeable zinc–manganese dioxide batteries that use mild aqueous electrolytes are attracting extensive attention due to high energy density and environmental friendliness. Unfortunately, manganese dioxide suffers from substantial phase changes (e.g., from initial α-, β-, or γ-phase to a layered structure and subsequent structural collapse) during cycling, leading to very poor stability at high charge/discharge depth. Herein, cyclability is improved by the design of a polyaniline-intercalated layered mangane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
880
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,232 publications
(919 citation statements)
references
References 46 publications
(60 reference statements)
33
880
2
4
Order By: Relevance
“…Taking the N‐MnO 2– x @TiC/C electrode for example, two main reduction peaks at around 1.32 and 1.2 V are noticed due to the intercalation reactions of H + and Zn 2+ into N‐MnO 2– x host . Typically, it is reported that the broad peak at 1.32 V corresponds to the reversible intercalation/deintercalation of H + into/from the interlayer of N‐MnO 2– x host . With the continuous insertion of H + , the pH of the electrolyte rises and results in the formation of zinc hydroxide sulfate (Zn 4 (OH) 6 SO 4 ⋅ x H 2 O) phase on the surface of N‐MnO 2– x , simply expressed as follows normalH2OnormalH++OH 4Zn+6OH+ 4SO42+ xnormalH2O Zn4normalOH6SO4xnormalH2O…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the N‐MnO 2– x @TiC/C electrode for example, two main reduction peaks at around 1.32 and 1.2 V are noticed due to the intercalation reactions of H + and Zn 2+ into N‐MnO 2– x host . Typically, it is reported that the broad peak at 1.32 V corresponds to the reversible intercalation/deintercalation of H + into/from the interlayer of N‐MnO 2– x host . With the continuous insertion of H + , the pH of the electrolyte rises and results in the formation of zinc hydroxide sulfate (Zn 4 (OH) 6 SO 4 ⋅ x H 2 O) phase on the surface of N‐MnO 2– x , simply expressed as follows normalH2OnormalH++OH 4Zn+6OH+ 4SO42+ xnormalH2O Zn4normalOH6SO4xnormalH2O…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, MnO 2 hosts are prone to suffer from structural instability during cycling process . Thus, the intrinsic electrochemical reactivity and structural stability of MnO 2 cathode must be reinforced to achieve high performance . In addition, the peripheral conductive design is equally essential for MnO 2 cathode to promote material utilization and high‐rate capacity by establishing rapid electron/ion transfer paths at the interfaces of electrolyte/MnO 2 and MnO 2 /current collector .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, most ion storage materials used in aqueous Li, Na, K‐ion battery can be employed as cathode materials in zinc‐ion batteries, such as manganese oxides, vanadium oxides, Prussian blue analogs, etc. Because of the high theoretical capacity (308 mAh g −1 based on single electron transfer between Mn 4+ and Mn 3+ ), nontoxicity, and abundance reserve, manganese oxide is the most widely investigated cathode material for zinc‐ion storage . As early as 1988, Zn/ZnSO 4 /MnO 2 rechargeable battery system was exploited by Yamamoto and co‐workers, but the mechanism of battery was unclear.…”
Section: Aqueous Batteries Using Multivalent Ions (Zn2+ Mg2+ Ca2+ mentioning
confidence: 99%
“…Rechargeable aqueous Zn‐based batteries are attractive for large‐scale energy storage (LSES), due to their low cost, high safety, and eco‐friendliness, as well as high ionic conductivity of the aqueous electrolyte . Among the most studied cathode materials, such as Prussian blue analogues and vanadium‐based oxides, manganese oxides are more promising for practical use of aqueous Zn ion batteries, attributing to both the high operating cell voltage and considerable capacity delivery . However, the structure collapse of MnO 2 (α‐, β‐, γ‐, etc.)…”
mentioning
confidence: 99%